Một số biện pháp dạy học chủ đề “Ba đường conic” (Toán 10) gắn với thực tiễn (RME) nhằm phát triển năng lực mô hình hóa toán học cho học sinh - Bùi Minh Khoa, Bùi Minh Khoa; Nguyễn Văn Thái Bình, Nguyễn Văn Thái Bình (Tạp chí Giáo dục, 2025)
According to the general education curriculum for Mathematics, one of the five core mathematical competencies that students need to develop is mathematical modeling competency. Teaching Mathematics according to Realistic Mathematics Education (RME) theory offers many opportunities to develop students' mathematical modeling competency through solving realworld situations. This paper proposes several teaching methods for the topic “Three Conic Sections” (Mathematics 10) to develop students' mathematical modeling ability, thereby helping them learn more actively, understand the meaning of mathematical models more deeply, and apply them to solve mathematical and real-world problems. To improve the effectiveness of teaching Mathematics according to RME theory, teachers need to increase the organization of situations related to real-world contexts, guide students to construct mathematical knowledge themselves; at the same time, the flexible use of teaching aids and tools will contribute to creating conditions for students to connect mathematics with real-world situations more effectively.